Pengaruh Kompensasi dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT Millennium Pharmacon International Cabang Jakarta 2 - Farida Safitri; Elmira Siska (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
PT Millennium Pharmacon International Branch Jakarta 2 is a company engaged in the distribution of pharmaceutical products, food supplements and medical devices with coverage throughout Indonesia, operating with 33 branch offices and 1 central warehouse. The problem related to work motivation is that employees feel they do not receive enough recognition for the achievements they have achieved. The aim of this research is to analyze the influence of compensation and work motivation partially or simultaneously on the performance of employees of PT Millennium Pharmacon International Jakarta Branch 2. The research method is to apply a quantitative design. Sampling was carried out using a saturated sampling technique for 48 employees. Data collection techniques through a Google Form questionnaire. The research methods used are validity test, linearity test, multiple linear regression test, t test, F test, and determination test. The results of this research show that compensation partially has a positive and significant effect on employee performance (tcount 8.072 > ttable 2.014). Partially, work motivation has a positive and significant effect on employee performance (tcount 2.995 > ttable 2.014). And simultaneously compensation and work motivation have a positive and significant effect on employee performance (Fcount 114.246 > Ftable 3.20).